An improved Channel Estimation Algorithm for Ultra- Wideband Wireless Communication Systems - Liu Jinhu; Mei Feihu (Institute of Advanced Engineering and Science, 2013)
Traditional DFT channel estimation algorithm is relatively balanced in terms of complexity and estimation performance, but compared with the four typical channels of UWB, especially in terms of CM1 and CM2 channel with a small number of the diameter, the cyclic prefix length is relatively much larger than the length of their delay, so the back part is still noise. Aimed at this problem, an improved DFT channel estimation algorithm is brought up in this paper, and this algorithm adds the appropriate threshold threshold in the CP to further eliminate noise, and simulation results show that the improved algorithm is better than the original algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2871